About the Influence of low-voltage electrical consumers on the sinusoidality of voltage and current - Abdurakhim D. Taslimov; Vakhobiddin U. Muminov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: in this article,the negative consequences of voltage and current sinusoidal disturbances in 0.38 kV electrical networks, including the occurrence of additional electrical energy losses in electrical network elements, are analyzed. The per capita consumption of electricity in the field of population and household services in modern rural areas with 0.38 kV was studied and the impact of voltage and current sinusoidality of electricity consumers of housing and utility enterprises in industrial districts and, in turn, non-sinusoidality on the quality of operation of electrical network elements is considered. The goal: assessment of the level of influence of household electricity consumers, which causes voltage and current non-sinusoidality in low-voltage power networks, on the quality indicators of electricity and additional power wastage, justification of technical means to reduce the level of non-sinusoidality in 0.38 kV power networks is considered Methods: systematic analysis of the influence of low-voltage electric consumers on the sinusoidality of the voltage and current in the electrical network, as well as the influence of the household and communal electric consumers on the sinusoidal of the voltage and current and to study and compare the experience of assessing the effect of non-sinusoidality on the performance quality of electrical network elements. Results: research results to determine the additional waste of power and electricity in non-sinusoidal operating modes of electric networks, as well as in the feasibility study and evaluation of measures aimed at improving the quality of electricity and saving energy.